The Relationship Between Sedentary Behavior, Back Pain, and Psychosocial Correlates Among University Employees - Hanna, Fahad; Daas, Rua N.; El-Shareif, Tasneem J.; Al-Marridi, Haneen H.; Al-Rojoub, Zaina M.; Adegboye, Oyelola A. (Frontiers in Public Health, 2019)
Objectives: This study aims to investigate the relationship between levels of sedentary behavior, physical activity and back pain and their psychosocial correlates among university employees. Methods: A cross-sectional study was conducted on both academics and non-academics professional staff at Qatar University employees. The data collection instrument was a combination of the International Physical Activity Questionnaire, the Global Physical Activity Questionnaire and the Acute Low Back Pain Screening Questionnaire. Results: A total of 479 (57% females) participated in the cross-sectional study. Two hundred and ninty three (61.2%) reported to have experienced back pain. The covariates adjusted odds ratios (aORs) showed that vigorous physical activity was protective variable for those who experienced lower back pain [aOR=0.84, 95%CI (0.56 – 0.98)], both lower and upper back pain [aOR=0.61, 95% CI (0.33 – 0.87)] and either lower or upper back pain [aOR=0.76, 95%CI (0.51 – 0.85)], respectively. Back pain was significantly higher in females than males (aORs: 1.37 to 2.21). Similarly, prolong sitting was significantly associated with those who experienced either LBP or UBP [aOR=1.74, 95% CI (1.19, 2.57)]. All back pain categories were found to be significantly associated with those who reported depressed mood. Conclusions: These findings suggest that sedentary type employees are exposed to increasing occupational hazards such as back pain and mental health issues. Strategies should aim at interrupting sitting time with planned and feasible physical activity interventions to be incorporated into the workplace health promotion policy to help prevent back pain, back injuries and mental health complications.